Boundary element method analysis of interface cracks between orthotropic layers - Neo, Melissa Lee Ting (2017)
The objective of this project is to investigate how varying material properties( η1and η2, the purely imaginary roots of the characteristic equation),crack-length to thickness ratio can affectthe stress intensity factors, phase angles and strain energy release rates of the interface cracks in bilayer orthotropic DCB and ELSbeam specimens.